2009
DOI: 10.1007/s00431-009-0940-1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors in children and adolescents living in an urban area of Southeast of Brazil: Ouro Preto Study

Abstract: This study aims to identify risk factors for cardiovascular disorders in schoolchildren living in Ouro Preto City, Brazil. A cross-sectional study was carried out in a population-based sampling of schoolchildren (6-14 years old), randomly selected and stratified by the proportion of students according to age and gender in each schools of the city. Biochemical, clinical and anthropometric variables as well as physical activity and family history were used in a logistic regression model for obesity or arterial h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1
17

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 39 publications
3
24
1
17
Order By: Relevance
“…Ademais, nossos resultados demonstraram associação positiva entre os níveis elevados de TG e dois importantes fatores de risco para doenças cardiovasculares: obesidade e sedentarismo, principalmente entre as crianças (< 10 anos). Este achado foi concordante com os de outros estudos brasileiros 3,28,29 . Altas concentrações de TG contribuem para o seu depósito na parede do vaso e o início do processo de acumulação do LDL-c, que está fortemente associado ao risco de desenvolvimento da aterosclerose 5 .…”
Section: Tabelaunclassified
“…Ademais, nossos resultados demonstraram associação positiva entre os níveis elevados de TG e dois importantes fatores de risco para doenças cardiovasculares: obesidade e sedentarismo, principalmente entre as crianças (< 10 anos). Este achado foi concordante com os de outros estudos brasileiros 3,28,29 . Altas concentrações de TG contribuem para o seu depósito na parede do vaso e o início do processo de acumulação do LDL-c, que está fortemente associado ao risco de desenvolvimento da aterosclerose 5 .…”
Section: Tabelaunclassified
“…O trabalho verificou, ainda, ao avaliar o PGC desses jovens em relação à idade, uma tendência de maior PGC nas crianças; no entanto, não houve diferença significativa entre as crianças e adolescentes, conforme observado por Cândido et al 20 em estudo prévio realizado com essa mesma população.…”
Section: Discussionunclassified
“…This scenario is also alarming in the age groups under 20 years (children and adolescents). Cândido et al 4 observed that schoolchildren aged 6-14 years residing in that city present a high prevalence of overweight (14.9%) and dyslipidemia, particularly in relation to total cholesterol (36.9%); they also observed an increase in the clustering of risk factors, which may indicate a higher risk of CVD in this population in the future.…”
Section: Introductionmentioning
confidence: 93%